80 Do Varied Omega-6: Omega-3 Ratio Diets Have Impact on Performance, Nutrient Digestibility, Blood Characteristics and Fecal E.coli and Lactobacillus Counts in Weaned Pigs. (10th April 2018) - Kim, J K; Upadhaya, S D; Zhang, W L; Yin, J; Kim, I H
Abstract: The supplementation of omega-3 fatty acid may improve the health status of weaned pigs that are faced with different stressors due to their effects on the immune system. Studies indicate that the balance between omega-6 and omega-3 fatty acid is a vital factor for health and longevity. The present study tested the hypothesis that altering the ratio of omega-6 (n-6) to omega-3 (n-3) fatty acid (FA) in the diet will improve growth performance, nutrient digestibility and blood parameters of weanling pigs. A total of 90 crossbred weanling pigs [(Yorkshire × Landrace) × Duroc, 28 days old] with an initial average body weight of 6.53 ± 0.71 kg were used in a 6-week experiment and randomly allotted to 1 of 3 dietary treatments [5 pigs per pen (2 barrows and 3 gilts); 6 pens per treatment.] in three phases. Treatments consisted of plant derived n- 6 and n-3 FA ratios (15:1, 10:1 and 5:1). Data were subjected to the statistical analysis as a complete randomized design using the GLM procedures of SAS and the pen was used as the experimental unit. Linear and quadratic polynomial contrasts were performed to determine the effects of n-6: n-3 FA ratios in the diet with P < 0.05 indicating significance. The supplementation of varied n-6: n-3 FA ratios in the diet showed linear increases (P < 0.05) in BW and average daily gain during phase 1 and 2. The feed: gain ratios reduced linearly (P < 0.05) during phase 1 and tended to reduce (P = 0.10) during phase 2 as the ratio of n-6: n-3 FA decreased from 15:1 to 5:1. However, the overall performance of weaners was not affected by the n-6: n-3 FA ratios. Dry matter and nitrogen and energy digestibility increased linearly (P < 0.05) with the reduction of n-6: n-3 FA ratio from 15:1 to 5:1 during week 3. In week 6, DM digestibility showed a significant linear increase (P < 0.05) whereas energy digestibility tended to increase with decreasing n-6: n-3 FA ratio in the diet. The high density lipid/cholesterol showed a significant linear increase (P < 0.05) at week 3 and a tendency to increase at week 6. In conclusion, the reduction of n-6: n-3 FA ratio from 15:1 to 5:1 in the diet did not affect the overall performance of weaning pigs. However, it showed a positive effect on the growth performance of pigs during phases 1 and 2.